Danantara in the Light of Legal Theories: A Normative Assessment of Indonesia’s Sovereign Wealth Fund - Princes, Elfindah; Silalahi, Wilma (APPS Publications, 2025)
The purpose of this study is to analyze the legal, ethical, and institutional dimensions of Danantara, Indonesia’s newly launched Sovereign Wealth Fund (SWF), using a multidimensional legal theoretical framework. This paper examines how the establishment of Danantara aligns with or deviates from core legal theories, and explores its implications for governance and public legitimacy. This study employs a qualitative, normative legal research method using a doctrinal approach. Primary and secondary legal sources were analyzed, including government regulations, official reports, academic literature, and media commentaries. The analytical framework is built upon five legal theories: Legal Positivism, Natural Law, Rule of Law, Critical Legal Studies, and Good Governance Theory. The findings show that while Danantara fulfills the requirements of formal legality, it suffers from a lack of societal legitimacy and accountability due to governance opacity, politically affiliated leadership, and absence of independent oversight. These issues highlight inconsistencies with ethical standards and democratic values promoted by the selected legal theories. This paper provides a unique comparative analysis of Danantara by integrating five major legal theories into a single analytical framework—an approach rarely applied to sovereign wealth funds. It contributes to legal scholarship by revealing how formal legal instruments may reproduce structural inequality and democratic deficits if not grounded in ethical and participatory principles.